Hierarchical fuzzy sliding mode control for a class of simo under-actuated systems - Vu Duc Ha; Huynh Xuan Dung; Nguyen Minh Tam; Nguyen Van Dong Hai (Journal of Technical Education Science, 2017)
In the paper, a hierarchical fuzzy sliding-mode controller (HFSMC) designing method is proposed. This method provides a simple way to achieve asymptotical stability and remove the chattering signal for a class of SIMO under-actuated systems with fuzzy control rules. This class of under-actuated systems is made from several subsystems. Based on this physical structure, the hierarchical structure of the sliding surfaces is designed as follows: at first, the sliding surface of every-subsystem is defined; then, the sliding surface of one sub-system is defined as the first layer sliding surface; the first layer sliding surface is used to construct the second layer sliding surface with the sliding surface of another subsystem. This process continues until the sliding surfaces of the entire subsystems achieve a suitable fuzzy controller which is built due to the final sliding surface to suppress chattering phenomenon of the system. Simulation results show the feasibility of this control method through two typical SIMO under-actuated systems.